Design and Validation of the Questionnaire for Organizational Factors Affecting the Transfer of Learning to the Workplace - khakrah, Fataneh; Malekian, Faramarz; Saeidipour, Bahman; Kavyani, Elham (Iranian Journal of Educational Sociology, 2022)
Purpose: The aim of this study was to design and validate the questionnaire of organizational factors affecting the transfer of learning to the workplace in Islamic Azad Universities of the west of Iran. Methodology: The method of data collection was mixed of sequential exploratory design type. Qualitative data was collected through semi-structured interview with 15 people including faculty members and specialists of training and human resource development who were selected through purposive sampling of theoretical and snowball sampling type. The analysis of qualitative data was carried out through grounded theory method. In quantitative section, researcher-made questionnaire was investigated by 11 experts and its relative content validity was calculated. In this way, the validity of the questionnaire was verified by the specialists and its reliability was calculated by Cronbach's alpha (0/873). Afterwards, the final version was distributed among 309 employees from the universities. To validate the designed tool, confirmatory factor analysis was used. SPSS and Lisrel software were used for this purpose. Finding: In the qualitative section, 25 components were identified which were presented in paradigmatic model template including 6 dimensions; causal conditions, core phenomenon, context conditions, intervening conditions, strategies and consequences. The quantitative stage results showed that fit indices, factor loads and t-values obtained from each criterion were fit and the 6 main dimensions and their factors had the ability to explain the variable of learning transfer. Conclusion: The organizational factors, especially organizational culture, have an important place in learning transfer due to their role as facilitator and stimulator.